2004
DOI: 10.1530/eje.0.1510343
|View full text |Cite
|
Sign up to set email alerts
|

Adult GH deficiency in Japanese patients: effects of GH treatment in a randomised, placebo-controlled trial

Abstract: Objective: To evaluate the influence of factors intrinsic to the Japanese population on consequences of growth hormone deficiency (GHD) and effects of GH treatment in adult Japanese hypopituitary patients with GHD. Study design: A 24-week, randomised, placebo-controlled, double-blind study in 64 patients in Japan, with GHD onset during adulthood (AO; n ¼ 27) or childhood (CO; n ¼ 37). Body composition measured by dual-energy X-ray absorptiometry (DXA) was evaluated centrally. Serum IGF-I, IGF binding protein-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
25
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 21 publications
12
25
1
1
Order By: Relevance
“…This was less pronounced in CO subjects, who exhibited the same pattern of IGF-I changes but at significantly lower levels. These results confirm a variety of studies in Caucasians [16][17][18] and also in Japanese [19], showing that adult CO GHD patients have lower baseline as well as GH-stimulated IGF-I levels than AO patients.…”
Section: Discussionsupporting
confidence: 89%
“…This was less pronounced in CO subjects, who exhibited the same pattern of IGF-I changes but at significantly lower levels. These results confirm a variety of studies in Caucasians [16][17][18] and also in Japanese [19], showing that adult CO GHD patients have lower baseline as well as GH-stimulated IGF-I levels than AO patients.…”
Section: Discussionsupporting
confidence: 89%
“…Despite various psychological and cognitive deficits, as well as an abnormal lipid profile and central adiposity, young patients with CO GHD who discontinue pediatric GH replacement exhibit only mild impairment of QoL when compared with GH-sufficient peers (14,15). Our CO patients have also consistently shown findings adverse to those characteristic of adult GHD, such as abnormal body composition and lipid profile at baseline (8). These findings may suggest another possibility, namely CO patients have adapted to the chronic effects of GHD during development and do not perceive their QoL as impaired (5,14,16) Responsiveness, defined as the ability to detect a change due to a treatment, is an important characteristic of a QoL instrument (17).…”
Section: Discussionmentioning
confidence: 71%
“…In previous reports on Japanese hypopituitary adults with GHD (8,9), it was demonstrated that the effects of GH replacement on body composition were comparable to those seen in Caucasian patients. QoL before and after GH replacement was assessed with the SF-36 in these studies, whose results have not been reported thus far.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations